Global perfusion assessment and tissue oxygen saturation in preterm infants: where are we? - Cerbo, Rosa Maria (Study of serum leptin in well differentiated thyroid carcinoma: Correlation with patient and tumor characteristics, 2013)
Near infrared spectroscopy (NIRS) monitoring is a new challenge for clinicians who deal with early detection of dangerous hypoperfusion in the brain, as well as in splanchnic and renal districts in critically ill preterm infants. Previous studies performed on infants and children with congenital heart disease, demonstrated the efficacy of this non-invasive method in managing hypoperfusive states pre, post and during cardiac surgery. Its use has improved post surgery outcome. NIRS monitoring has been used also to assess therapeutic intervention utility.